Possibilities of increasing renewable energy in Croatia, Slovenia and Slovakia - wood pellets : Mogućnosti povećanja obnovljivih izvora energije u Hrvatskoj, Sloveniji i Slovačkoj - drvni peleti - Pirc, Andreja (Array, 2020)
Energy from renewable sources is globally a very important issue. In order to reduce pollution and greenhouse gas emissions, many countries enact laws for enhancing the consumption of renewable energy sources. Sooner or later traditional non-renewable energy sources would have to be replaced with alternative energy sources that are already used in developed countries. According to the European Commission (2018), the EU is already a global leader in the sustainable use of natural resources within an efficient bio-economy. The wood pellet industry is becoming more important and the use of wood pellets is increasing as one of the most important contributors to the renewable energy goals of the EU. Wood pellet is an environmentally acceptable product and its production contributes to desirable rural development and sustainable approach to the management of timber resources. This paper focuses on the market of wood pellets used for heating, pinpointing differences in consumers point of view, and drafting the possibilities of future consumption enhancement. Results revealed a relatively low use of wood pellets in all the three surveyed markets. The highest share of consumers of wood pellets came from the areas with less than 5,000 inhabitants. Such households were mostly over 20 years old. The most important factors to decide to use such source of energy were space (required for the heating system) followed by price of wooden pellets.